Sharing Photographs on Instagram Boosts Students’ Self-Confidence in Speaking English - Rayinda Eva Rahmah (Jurnal Pedagogy, 2018)
This paper reports on the way in which posting photographs in a social media, Instagram, used as a strategy to boost confidence in speaking English among students majoring English education in IAIN Pekalongan. Confidence is seen to influence learners’ achievement in communication skills. The qualitative outcomes deriving from five participants revealed positive impacts of the Instagram usage on their confidence in speaking English. Therefore, this study uses qualitative research with the instruments of data collection using interview. The finding shows that sharing photographs on Instagram can contribute to the students’ confidence to speak in a foreign language. The positive results offered some insightful suggestions and implications for teaching English as a foreign language.